KINERJA HUMAS PENGADILAN NEGERI PEKANBARU DALAM MEMBERIKAN INFORMASI KEPADA MASYARAKAT - Nuriati Putri; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Public Relations performance in the Pekanbaru District Court is less effective in providing information to the community, one of which is due to limited public relations capacity and too heavy workload, Public Relations of the District Court which concurrently serves as a Judge. The purpose of this study is: to find out the form of Public Relations Performance of the Pekanbaru District Court in providing information to the public and to find out the barriers to the Performance of Public Relations of the Pekanbaru District Court in providing information to the public.     The design used in the study is a descriptive approach. In this study researchers used a qualitative descriptive type, this research will be conducted in the city of Pekanbaru, the data relating to this study will be obtained from the Pekanbaru City District Court. In collecting data, researchers used interviewing, observation, and documentation techniques by using informants as sources of information.               The results of the study show that the Public Relations of the Pekanbaru District Court is in charge of providing information related to policies, activities, reports on achievements or achievements, as well as information related to postponement hearings or changes to the trial schedule to the public. Public Relations also received complaints and complaints from the public. As a development and creator of an organization's positive image, namely by providing services openly to the community. The obstacles experienced in providing information include: Information received by the Public is not in accordance with what has been scheduled, Mass communication, namely the delivery of information is not widely conveyed to the public.